Prophylactic supplementation of vitamin E and selenium influences the level of antioxidant vitamins during endotoxic shock - SANDHU, TAJBIR SINGH; SINGHA, SATINDER PAL SINGH (The Indian Journal of Animal Sciences, 2014)
Male buffalo (Bubalus bubalis) calves were used to study the effect of prophylactic supplementation of vitamin E and Se on the circulating antioxidant vitamins during endotoxic shock. Male calves (15), 6-12 month old, were divided into 3 groups of 5 animals each: Group 1-control, group 2-cndotoxic shock, group 3-supplemented with vitamin E @ 250 mg and se @ T:5 mg at weekly interval through intramuscular route, one montfi prior to induction of endotoxic snock. All theÂ animals in groups 1 and 2 exhibited signs of endotoxic shock. Prophylactic supplementation with vitamin E and Se resulted in significant increase in normal (0 hr) circulating plasma levels of vitamin E and Bita-carotene whereas plasma vitamin C decreased. There was significant increase in the lipid perox’idation levels during the shock. Lipid peroxidation level was lower in group 3 as compared to group 2 at every stage of study up to 72 hr. The circulating levels of vitamin E, vitamin C and Bita-carotene reached a lower level and then showed a tendency to increase toward the 0 hr value. Prophylactic supplementation with vitamin E and Se was successful in delaying the onset of oxidative damage during endotoxic shock as well as accelerating the recovery from shock by quenching the free radicals.